PEMBAHARUAN HUKUM KEBERADAAN HUKUMAN MATI BAGI PELAKU KORUPSI - Zakiy Bima Kusuma Aliyan; Elfrida Ratnawati Gultom (Halu Oleo University, 2023)
This paper raises the issue of the existence of the death penalty in the Law of the Republic of Indonesia No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Corruption Crimes and the concept of the death penalty for perpetrators of corruption. The criminal act of corruption is classified as a special crime that needs to be dealt with firmly. Severe punishment is needed to limit this crime from becoming more rampant, such as the death penalty which is the most severe punishment in criminal law. This study discusses the implementation of the death penalty in Indonesia in accordance with the law and explains the threat of the death penalty in the Corruption Crime Act, especially in Article 2 paragraph (2). The research uses primary legal sources, secondary legal sources, and tertiary legal sources the data collection method used is document and legal research by conducting legal analysis of existing laws and regulations related to criminal penalties for criminal acts of corruption, also researching legal reforms in the new Criminal Code related to death penalty reform.